2023
DOI: 10.3390/ijerph20021260
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Enacted Sexual Stigma toward Gay and Bisexual Men in the Military: The Enacted Sexual Stigma Experiences Scale in Military Service

Abstract: Gay and bisexual military servicemembers experience disproportionately high rates of victimization due to enacted sexual stigma (ESS). This study formulated a new scale, called the Enacted Sexual Stigma Experiences Scale in Military Service (ESSESiMS) for gay and bisexual servicemembers, and examined its psychometric propensities. The five-item ESSESiMS was first developed based on the results of focus group interviews with 12 participants. A total of 399 gay and bisexual men who have experience of the militar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Although traditionally, some research has shown SD as a construct that is found on the opposite side to sexual pleasure ( Snyder & Berg, 1983 ), more recently, they have been considered as independent constructs that require individual attention for the creation of evaluation measures that are not interchangeable or for the prevention the overlapping of the effectiveness of the treatments developed for sexual dysfunctions ( Stephenson & Meston, 2010 ). The SD has not only been shown to be present in various populations ( Lin et al, 2023 ; Lin et al, 2017 ; Lin et al, 2022 ) but has also been shown to be associated with negative impacts on the sexual life of individuals with relevant medical conditions (e.g., endometriosis, dyspareunia, epilepsy, prostate cancer, and heart disease; Lin et al, 2020 ; Lin et al, 2022 ; Privitera et al, 2023 ; Saffari et al, 2017 ; Santos-Iglesias et al, 2020 ). Although there are no data in Colombia regarding the relationship between sexual functioning and SD, the fact that around 44.6 % of cisgender women and 33.5 % of cisgender men may experience a possible difficulty related to their sexual functioning ( Marchal-Bertrand et al, 2016 ) can highlight the importance of timely detection of SD in the Colombian population.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditionally, some research has shown SD as a construct that is found on the opposite side to sexual pleasure ( Snyder & Berg, 1983 ), more recently, they have been considered as independent constructs that require individual attention for the creation of evaluation measures that are not interchangeable or for the prevention the overlapping of the effectiveness of the treatments developed for sexual dysfunctions ( Stephenson & Meston, 2010 ). The SD has not only been shown to be present in various populations ( Lin et al, 2023 ; Lin et al, 2017 ; Lin et al, 2022 ) but has also been shown to be associated with negative impacts on the sexual life of individuals with relevant medical conditions (e.g., endometriosis, dyspareunia, epilepsy, prostate cancer, and heart disease; Lin et al, 2020 ; Lin et al, 2022 ; Privitera et al, 2023 ; Saffari et al, 2017 ; Santos-Iglesias et al, 2020 ). Although there are no data in Colombia regarding the relationship between sexual functioning and SD, the fact that around 44.6 % of cisgender women and 33.5 % of cisgender men may experience a possible difficulty related to their sexual functioning ( Marchal-Bertrand et al, 2016 ) can highlight the importance of timely detection of SD in the Colombian population.…”
Section: Introductionmentioning
confidence: 99%